MIDDLE EAR DISEASES AND THE EFFICACY OF VENTILATION TUBE INSERTED IN TO OTITIS MEDIA IN CHILDREN WITH CLEFT PALATE - Tăng, Xuân Hải; Phan, Quang Trung; Ha, Cuc; Tran, Minh Long (Tạp chí Tai Mũi Họng Việt Nam, 2024)
Objectives: Cleft palate is associated with middle ear diseases, but the magnitude of this problem is not generally well appreciated. This study aimed to describe the middle ear status and to evaluate the results of ventilation tube insertion in children with cleft palate.Methods: A cross-sectional cohort study was conducted to investigate 78 children with cleft palate (CP). These patients underwent otoscopy and tympanometry to assess middle ear status. When chronic otitis media with effusion (OME), recurrent otitis media, or atelectasis were diagnosed, ventilation tube insertion (VTI) and palatal repairation were performed simultaneously. The study was carried out in Nghe An Obstetrics and Pediatrics Hospital from January 2023 to December 2024.Results: The sex ratio was 1:1; the mean age of the patients was 34.59 months (13 months – 13 years old). Middle ear diseases occurred in 60.26% of patients with Cleft palate, with the incidence of OME and atelectasis being 30.76% and 24.35%, respectively. Type B tympanograms were most frequently observed (66.23%). The rate of post-VTI otorrhea was 10.34%, while the rate of tube extrusion after 3 months was 8.66%.Conclusions: We assessed the efficacy of ventilation tube insertion (VTI) in eliminating otitis media with effusion (OME) in patients with Cleft palate undergoing palatal repair. The results indicated that VTI is effective in eliminating OME in these patients.